2014
DOI: 10.1371/journal.pone.0093905
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Autoantibodies against Transthyretin for the Screening and Diagnosis of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic, autoimmune, systemic and inflammatory rheumatic disease that leads to inflammation of the joints and surrounding tissues. Identification of novel protein(s) associated with severity of RA is a prerequisite for better understanding of pathogenesis of this disease that may also have potential to serve as novel biomarkers in the diagnosis of RA. Present study was undertaken to compare the amount of autoantigens and autoantibodies in the plasma of RA patients in comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
2
16
0
1
Order By: Relevance
“…As shown in our study, many JIA patients have significantly increased levels of TTR and anti-TTR antibodies in the SF as well as in the plasma (23, 24, 48). Considering the tendency of TTR to precipitate and aggregate, even a small increase in TTR synthesis or half-life could easily bring the protein out of solution (4446).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As shown in our study, many JIA patients have significantly increased levels of TTR and anti-TTR antibodies in the SF as well as in the plasma (23, 24, 48). Considering the tendency of TTR to precipitate and aggregate, even a small increase in TTR synthesis or half-life could easily bring the protein out of solution (4446).…”
Section: Discussionsupporting
confidence: 72%
“…Prior to any experiment, SFs were digested with hyaluronidase (30 kU/ml) as previously described (24) and depleted of albumins and IgG using Aurum Serum spin columns (Bio-Rad). Total protein concentration from human SF was determined using the Bradford assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…A pilot study showed that transthyretin levels were upregulated in the sera of paediatric SLE patients compared to healthy controls . Additionally, increased serum levels of transthyretin were associated with the severity of rheumatoid arthritis, suggesting a role in disease pathogenesis . The main biological role of Hp is to bind haemoglobin, prevent iron loss and subsequent kidney damage during haemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, autoimmune diseases such as RA are characterized by destruction of the synovium following an autoimmune response. Transthyretin is reported to be one of the targets attacked by autoantibodies . The role of transthyretin has not yet been defined, and research on how transthyretin is associated with the immune response is ongoing.…”
Section: Discussionmentioning
confidence: 99%